The Public Policy Dynamics of Increasing Health Insurance Rates in a Developing Country - Wibawa, Fahmi; Madya, Faizal (KnE Social Sciences, 2022)
Health insurance plays an important role in the COVID-19 pandemic. As a part of public policy, examining increasing health insurance contributions in developing countries is important to understand the dynamics, formulation processes, pros and cons, and implications for public participation. This study considered the increasing contributions of Indonesia Health Insurance (BPJS) and the findings indicated that the government faces a dilemma. On one side, the income of citizens is relatively diminished due to the restrictions on mobility as a result of the pandemic. On the other side, during the pandemic, health services need to perform well. Considering that health insurance is part of a national social security system, which is a common feature in developing countries, public health costs should be the responsibility of the State. Therefore, the increase in the BPJS Kesehatan rate needs to consider the ability of the citizen, and also ensure a positive impact on improving health services for the citizen. Keywords: public policy dynamics, public participation, positive impact